2018
DOI: 10.1155/2018/8572371
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and Treatment Decisions for Dental Erosive Wear: A Questionnaire Survey among Icelandic Dentists

Abstract: Dental erosive wear (DEW) is common among children and adolescents, and a survey of Icelandic children showed that 30.7% of 15-year-olds were diagnosed with the condition. Objective. To gain knowledge about dental practitioners' experiences, opinions, and treatment decisions. Materials and Methods. A precoded questionnaire, previously used among Norwegian dentists, was sent electronically to all dentists in Iceland (n = 341). Results. The response rate was 64.2%, and 58% of dentists were male. More than half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 42 publications
10
29
2
1
Order By: Relevance
“…Here, as much as 80% of the respondents never measure the saliva secretion rate. The corresponding rates in the Icelandic and Norwegian surveys were 65% and 73% [8,9].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Here, as much as 80% of the respondents never measure the saliva secretion rate. The corresponding rates in the Icelandic and Norwegian surveys were 65% and 73% [8,9].…”
Section: Discussionmentioning
confidence: 87%
“…The questionnaire was used previously in similar studies in Norway in 2012 [8] and in Iceland in 2018 [9]. The original questionnaire was translated into English by a Norwegian research group, and the English version was translated into Finnish by two of the authors (TT, VA).…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from Norway and Iceland have indicated that dentists generally are well educated with respect to diagnosis and treatment of ETW although dietary and salivary analyses had low priority. (Mulic, Árnadòttir, Jensdottir, & Kopperud, 2018; Mulic, Vidnes‐Kopperud, Skaare, Tveit, & Young, 2012). A recent questionnaire among dentists from Germany displayed that the decision‐making was mainly dependent on the lesion depth, size of affected surfaces and the presence of pain (Kanzow, Biermann, & Wiegand, 2019).…”
Section: Introductionmentioning
confidence: 99%